Applications of tagging and mapping insect resistance loci in plants - Yencho, G.C.; Cohen, M.B.; Byrne, P.F. (Annual Reviews, 2000)
This review examines how molecular markers can be used to increase our understanding of the mechanisms of plant resistance to insects and develop insect resistant crops. We provide a brief description of the types of molecular markers currently being employed, and describe how they can be applied to identify and track genes of interest in a marker-assisted breeding program. A summary of the work reported in this field of study, with examples in which molecular markers have been applied to increase understanding of the mechanistic and biochemical bases of resistance in potato and maize plant/pest systems, is provided. We also describe how molecular markers can be applied to develop more durable insect-resistant crops. Finally, we identify key areas in molecular genetics that we believe will provide exciting and productive research opportunities for those working to develop insectresistant crops.